2018
DOI: 10.5539/ijef.v10n12p135
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Governance on Working Capital Management Efficiency: Evidence from the Listed Companies in the Consumer Services Sector in Botswana

Abstract: The paper presents the findings of the analysis of the impact of corporate governance mechanisms on working capital management efficiency in the listed companies of the Consumer service sector in Botswana. Eight corporate governance elements and seven working capital components were extracted from the annual reports of a sample of six companies for the period 2012 to 2017 for the analysis. Thirty six observations were obtained. Pearson correlations were executed to determine the relationship between corporate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
2
4
0
2
Order By: Relevance
“…They evidently showed that the value of cash is approximately doubled in by well-governed firms compared to firms with poor or weak corporate governance and poorly-governed firms also dissipate cash more quickly and less effficiently. The same finding was reached in the study by Sathyamoorthi, Mbekomize, Mapharing, and Selinkie (2018) as they claimed that the number of non-executive directors has a significantly negative correlation with the net operating cycle. Our hypothesis is proposed as follow: H3: Board independence has a positive impact on firm's solvency…”
Section: Board Independencesupporting
confidence: 78%
See 2 more Smart Citations
“…They evidently showed that the value of cash is approximately doubled in by well-governed firms compared to firms with poor or weak corporate governance and poorly-governed firms also dissipate cash more quickly and less effficiently. The same finding was reached in the study by Sathyamoorthi, Mbekomize, Mapharing, and Selinkie (2018) as they claimed that the number of non-executive directors has a significantly negative correlation with the net operating cycle. Our hypothesis is proposed as follow: H3: Board independence has a positive impact on firm's solvency…”
Section: Board Independencesupporting
confidence: 78%
“…On an average, a manufacturing firm in Ho Chi Minh City Stock Exchange gives its credit customers 111 days (equivalent to nearly 4 months to pay off their debts while it is offered by the suppliers or creditors for a credit term of just only 46 days. The days of accounts receivables in Vietnamese manufacturing companies is much longer than that in the listed companies in Botswana (10 days) and America (50 days), signifying the inefficient management of receivables (Gill & Biger, 2013;Sathyamoorthi, Mbekomize, Mapharing, & Selinkie, 2018). That might be the reason for the high level of debts and liabilities employed by those companies as their mean of debt ratio is at 1.5.…”
Section: Data Collection and Variable Descriptionmentioning
confidence: 97%
See 1 more Smart Citation
“…GCG perlu diterapkan dalam perusahaan agar dapat memberi nilai tambah bagi perusahaan serta pihak-pihak yang berkepentingan. GCG yang efektif dapat diterapkan dengan bertanggung jawab melindungi dan meningkatkan kekayaan yang telah diinvestasikan pada perusahaan (Sathyamoorthi et al, 2018). Menurut peraturan menteri BUMN PER-01/MBU/201 terdapat prinsip-prinsip yang perlu diterapkan BUMN guna memaksimalkan nilai BUMN.…”
Section: Good Corporate Governance (Gcg)unclassified
“…Hal tersebut sejalan dengan penelitian dari Ningsih et al (2019) bahwa peningkatan jumlah anggota dewan direksi akan meningkatkan kinerja keuangan. Rumus untuk menghitung dewan direksi menurut Sathyamoorthi et al (2018) adalah sebagai berikut.…”
Section: Dewan Direksiunclassified